2016
DOI: 10.14423/smj.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

Does Timing of Internal Medicine Residency Interview Affect Likelihood of Matching?

Abstract: Interviews When should I plan on scheduling interviews with residency programs? (Louis Binder, MD) The heaviest interview months for residency interviews in Emergency Medicine are in December and January. Some residencies may extend interview invitations earlier (October or November) to especially well qualified applicants, to students already on site undertaking away electives at that institution, or to applicants well known to the institution (i.e. students from their home school, repeat applicants, or those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Given that the candidates' preferences are weighted higher in the Match algorithm, we suspect this would not have an impact on matching probability; however, our data set does not include the final Match results necessary to assess this potential relationship. Studies looking at Internal Medicine, and Anesthesiology residency interviews found no correlation between interview date and whether an applicant will match at a particular institution 21,22 . A study published which looked at the 2014‐2015 interview season for eleven residency specialties at a single institution found interview timing had no relationship with being ranked or matching 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that the candidates' preferences are weighted higher in the Match algorithm, we suspect this would not have an impact on matching probability; however, our data set does not include the final Match results necessary to assess this potential relationship. Studies looking at Internal Medicine, and Anesthesiology residency interviews found no correlation between interview date and whether an applicant will match at a particular institution 21,22 . A study published which looked at the 2014‐2015 interview season for eleven residency specialties at a single institution found interview timing had no relationship with being ranked or matching 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the timing of residency interviews and the likelihood to match; no statistically-significant relationships were noted in these studies. Studies have been performed in internal medicine [ 5 ], anesthesia [ 6 ], emergency medicine [ 7 ] and a larger review of multiple specialties [ 8 ]. These studies tended to group interview dates into broad categories of early, middle, and late interviews, and then determined if there were any correlations to the residency match.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these can independently influence a candidate’s match outcome [ 9 , 10 ]. Previous studies [ 5 8 ] of the temporal effects on residency interviews did not examine interview scores assigned to applicants; these effects may, in fact, represent a better understanding of the temporal effects of interview timing given that it removes several of the aforementioned confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The scheduling of residency interviews is a time-sensitive process that often rewards quick responders with preferred dates and times. Evaluation of the residency match in internal medicine, 25 emergency medicine, 26 and 10 additional specialties showed that there was no correlation between interview date and a successful match. 27 Other external factors including time of day have not been well studied in the interview process.…”
mentioning
confidence: 98%